Manual do planejamento, construção e manutenção do tesauro Unesp para bibliotecas do conceitual a práxis - Fujita, Mariângela Spotti Lopes (Editora Oficina Universitária, 2021)
A thesaurus building and maintenance manual for libraries is unusual because it is not common for libraries to build thesauri and keep them up to date. However, we believe that this practice is necessary in view of the constant need to update specialized and multidisciplinary vocabulary required by scientific dissemination. This book was conceived along the lines of the development of the Unesp Thesaurus creation and was organized to mirror the planning and organization of a thesaurus in the context of university libraries. Like other libraries, university libraries are subject to digital technological evolution that affects library practices in a special way and forces them to constantly reinvent themselves. Therefore, many of the solutions presented in this book respect the ideal conditions for this renewing change, but also respect its feasibility conditions.